Integration of RULA and REBA methods in material handling processes with tool manufacturing at PT XYZ - Oki Widhi Nugroho; Aditya Ferdy Alamsyah; Ade Irpan Sabilah (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Construction projects, in their operations, face numerous risks of work accidents, ranging from minor to severe. Workers are less aware of the importance of using PPE, so violations of OHS requirements are still often found by workers, even though they have implemented OSHMS. This study aims to evaluate ergonomic risks in manual material handling and propose ergonomic aids to reduce these risks in construction projects. The method used in this study is a gap analysis of the OHS control dashboard approach. The results of the study obtained the results of the implementation of OHS in construction projects on the dashboard at 82.14%, which means that workers or organisations are ready to comply with OHS requirements standards. In the measurement and monitoring of OHS in construction projects, it was found that the number of OHS violators was 5 people out of a total of 28 workers who were working at that time. The OHS dashboard content consists of the results of questions related to safe work requirements such as PPE, equipment and materials, procedures and controls, and the work environment. The researcher hopes that the method, as demonstrated in the results of this study, can be applied and further developed.